PENGARUH DATA VAKSINASI, INDEKS DOW JONES DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA PERIODE TRIWULAN SATU TAHUN 2021 - Simamora, Saur Costanius (Feb Universitas Dirgantara Marsekal Suryadarma, 2021)
This study aims to determine The Effect of vacination, Dow Jones Index and Exchange Rate on the join share price index (JCI) in Indonesia Stock Exchange in quarter 1 year 2021. Samples were taken using purposive sampling technique. Numbers of sample are 43 days since the first vaccination by the goverment. The methods used for collecting data were documentation or secondary data. And for analysis technique used is multiple linear regression analysis and classic assumption test.Based on the results of the T test, it was concluded that vaccination data had a negative and significant effect on IHSG, Exchange Rate and Dow Jones Index had a positive and significant effect on IHSG. Based on the F test it was concluded that vaccination data, Exchange Rate and Dow Jones Index had a positive significant effect.Â Keywords: Vaksinasi Covid-19, Indeks Dow Jones, Nilai Tukar, IHSG